Optimising conservation tillage systems for wheat and oilseed rape production. - Giannitsopoulos, Michail (Cranfield University, 2017)
The aims of the thesis are to determine the effect of different conservation tillage systems on the agronomic, environmental and economic performance of a wheat and oilseed rape rotation, and to understand the processes involved so that the systems can be improved. The field research examined five systems over three seasons (September 2013 to August 2016) in two fields (one clay and one clay loam) in Northamptonshire. The most disruptive tillage treatment was the Farm system comprising the use of a Sumo Trio when establishing oilseed rape, and the Sumo Trio and a Kuhn seed drill when establishing wheat. The least disruptive system was a Väderstad Seed Hawk or Rapid. The other three treatments were all one pass conservation tillage systems comprising a Claydon Hybrid Drill, a Mzuri Pro til 3, and a Sumo Deep Tillage Seeder (DTS). To understand the effect on draught and soil disturbance, specific components of the systems were tested under controlled conditions at Cranfield University’s soil bin facility. The shallow working Väderstad required the lowest draught and disturbed less soil than deep working treatments. A low aspect ratio (working depth/implement width) and rake angle reduced the draught. In the field immediately after tillage, the Farm system showed the greatest reduction in bulk density and penetration resistance at 0-50 mm and 150-200 mm, but this effect was not maintained during the season. The level of surface residue was lowest (15%) with the Farm system and greatest (75%) with the Väderstad. The shallow Väderstad led to the highest earthworm abundance in all years and both fields, proportions of water stable aggregates and microbial biomass carbon in third and first year respectively. In the clay field, blackgrass infestation doubled from 8.2% in 2013-14 to 16.0% in 2015-16; it was not a major problem in the clay loam field. Due to high variability, there was no significant effect (p>0.05) of tillage treatments on the yield of wheat and oilseed rape over the 3-year trial period in either field, except when delayed drilling of oilseed rape with the Sumo DTS in September 2015 which led to reduced yields. At a reduced significance level of p=0.15, higher yields observed for Väderstad and Mzuri in the clay soil were associated with higher levels of organic matter. The relative profitability of the five systems was primarily determined by the assumed yields and secondly by the cost of the systems. The predicted annual net margin for the five systems varied from £545 to £659 ha¯¹. The calculated cost of the five tillage systems (assuming working areas ranging from 370 to 1,100 ha) ranged from £11 to £31 ha¯¹ a¯¹, with the lowest cost achieved by the 6 m Claydon system. Assuming blackgrass weeds are not an issue, shallow low disturbance systems can result in low costs, improved soil biology and carbon storage, and sustainable high yields.